Methods for a neoliberal order: views on Yemen. (January 2019) - Aboul-Ela, Hosam
In Barbara Harlow's last works, there was a distinctive methodological shift as she confronted the new realities of the post-9/11 world. The implications of this methodological movement are explored in this article through a reading of the history of the Yemeni city of Aden. Aden's history – as a protectorate, an Arabic-speaking port, a virtual city-state and a link to East Africa – suggests the ways in which historical particularity often fits the colonial discourse paradigm imperfectly. Aden also later became a centre of radical anti-colonial solidarity in the 1970s, a centre of extreme jihadi activity during the war on terror and, most recently, a site of catastrophe manufactured by global elites. This historical trajectory also calls for a critical accounting of new methods and approaches for addressing the inequalities of the contemporary global order.